(untitled) (Global Conference on Medical and Health Sciences, 2026)
Targeted drug delivery systems represent a major advancement in modern oncological treatment strategies. Nanobiophysics provides a quantitative framework for understanding nanoparticle–cell interactions, membrane transport mechanisms, and controlled therapeutic release dynamics. The present study evaluates the biophysical properties of engineered nanoparticles designed for targeted cancer therapy and analyzes their efficiency through computational modeling and experimental parameter simulation.